DEVELOPMENT OF WOMEN’S ENTREPRENEURSHIP IN UZBEKISTAN IN THE CONTEXT OF THE DIGITAL ECONOMY - Qanoatova Feruza Bobokulovna (Western European Studies, 2025)
The article says that a number of normative acts have been adopted to strengthen the position of women in the country, guarantee their rights and freedoms, through these norms create effective mechanisms for women's entrepreneurship
Keywords: people; women; reform